DIAGNOSTIC ACCURACY OF SALINE HYSTEROSONOGRAPHY IN DETECTING ENDOMETRIAL HYPERPLASIA IN PATIENTS WITH POST MENOPAUSAL BLEEDING - Benish Yousuf; Hira Ambreen; Tahira Mariam; Abdul Raouf; Ambreen Yaseen; Rabia Aslam; Muhammad Ahsan (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVE: Saline hysterosonography is a simple and cost-eﬀective method with high sensitivity to detect uterine abnormalities causing postmenopausal bleeding. The objective of this study was to evaluate the diagnostic accuracy of saline hysterosonography in detecting endometrial hyperplasia in women with postmenopausal bleeding by taking histopathology as a gold standard. METHODOLOGY: A hundred and twenty (120) cases were enrolled from the outpatient and inpatient department of obstetrics and gynecology. Proper history and relevant examination of the patient was done. Then preparations were made for the procedure. The patient was counseled and the technique explained to her. Then Foley catheter no 12 was passed in cervix and sonography was done while instilling normal saline through a cervical catheter and scan pictures were frozen and results were given by expert gynecologist of Allied Hospital, Faisalabad. Histopathology specimen was sent to the pathology lab. RESULTS: Sensitivity, speciﬁcity, positive predictive value, negative predictive value, and diagnostic accuracy of saline hysterosonography in detecting endometrial hyperplasia was recorded as 96.15%,91,49%,75.76%,98.85%, and 92.5% respectively. CONCLUSION: Saline hysterosonography has high sensitivity to detect uterine hyperplasia. It can be used as a cost eﬀective alternative to hysteroscopy in many units in Pakistan.